2020
DOI: 10.1177/1477878520980197
|View full text |Cite
|
Sign up to set email alerts
|

Children’s wellbeing and their academic achievement: The dangerous discourse of ‘trade-offs’ in education

Abstract: Research conducted in England over the last decade has documented sustained, significant decreases in children’s wellbeing. While recent changes to curriculum policy promoting children’s wellbeing have been introduced, a notable feature of the discourse surrounding the promotion of children’s wellbeing is that wellbeing is regarded as opposed to, or in tension with, children’s academic achievement. Recently, Gabriel Heller-Sahlgren proposed that there is an inevitable ‘trade-off’ between children’s ‘wellbeing’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 122 publications
(141 reference statements)
0
45
0
Order By: Relevance
“…These mixed evidences concerning the relationships between different dimensions of student well-being and academic achievement offer insights in promoting well-being simultaneously and aiming for achievement improvement. However, the reasons behind these mixed evidences in this study need further investigations ( Clarke, 2020 ).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…These mixed evidences concerning the relationships between different dimensions of student well-being and academic achievement offer insights in promoting well-being simultaneously and aiming for achievement improvement. However, the reasons behind these mixed evidences in this study need further investigations ( Clarke, 2020 ).…”
Section: Discussionmentioning
confidence: 75%
“…To sum up, although, with inconsistent results, most studies found a positive “trade-off” existing between well-being and achievement ( Clarke, 2020 ). However, the majority of these studies only measured a single dimension of student well-being and its relationship with academic outcomes within a single subject.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations